Electrolyte and secondary battery
By adding spirodienone sulfonyloxazole compounds to the electrolyte of lithium-ion batteries, the problem of easy oxidation of high-nickel positive electrode materials at high temperatures is solved, forming a stable solid-state interface film, significantly improving the high-temperature storage performance and thermal impact performance of the battery.
Patent Information
- Application Number
- CN202411842438.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-18
AI Technical Summary
High-nickel positive electrode materials are easily oxidized at high temperatures, resulting in electrolyte decomposition and transition metal dissolution, affecting the high-temperature storage stability, cycle stability and thermal shock performance of lithium-ion batteries.
An electrolyte with a spirodienone sulfonyloxazole compound is used. The lonely electron pair on N atoms in the heterocyclic structure of the compound is Lewis basic, inhibiting the damage of HF to the electrode interface, and forming a stable solid interface film on the positive electrode surface to stabilize the transition metal and reduce oxidation.
It significantly improves the oxidation resistance of the electrolyte, reduces the high-temperature gas production of the battery, and improves the high-temperature storage, circulation and thermal shock performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to an electrolyte and a secondary battery. Background Art
[0002] At present, the market prospects for power lithium-ion batteries for electric vehicles are broad. In many application fields, people have put forward higher requirements for the endurance of lithium-ion batteries. In order to improve the energy density of lithium-ion batteries, developing lithium-ion battery positive electrode materials with high specific capacity is one of the effective methods. High-nickel positive electrode materials have become a research hotspot due to their high theoretical specific capacity compared to other positive electrode materials. However, the high nickel metal content in high-nickel positive electrode materials makes them highly oxidizing, causing the electrolyte to easily undergo electrochemical oxidation reactions on the positive electrode surface, while causing changes in the structure of high-nickel positive electrode materials, causing transition metals such as nickel and cobalt to undergo reduction reactions and dissolve, resulting in serious gas production during high-temperature storage, affecting the high-temperature storage stability, high-temperature cycle stability and thermal shock performance of the battery. Summary of the invention
[0003] The present application provides an electrolyte and a secondary battery, which aims to solve to a certain extent the problem of high-nickel positive electrode material surface being easily oxidized in existing lithium-ion secondary batteries, resulting in serious gas production during high-temperature storage, affecting the high-temperature storage stability, high-temperature cycle stability and thermal shock performance of the battery.
[0004] In a first aspect, the present application provides an electrolyte, the electrolyte comprising a solvent, an electrolyte salt and a compound having a structure shown in Formula I:
[0005]
[0006] In Formula I, R1 is selected from unsubstituted or substituted C5 to C 15 aryl or unsubstituted or substituted C3~C 15 The heteroaryl group is selected from O, S, N or P; "substituted" means that the hydrogen atoms on the group are selected from halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy, C1-C 10substituted by one or more of the haloalkyl of 1-C3; preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl, unsubstituted or substituted thienyl or unsubstituted or substituted furanyl, "substituted" means that the hydrogen atoms on the group are substituted by one or more selected from halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; more preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl or unsubstituted or substituted thienyl, "substituted" means that the hydrogen atoms on the group are substituted by F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl;
[0007] R2 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 Preferably, R2 is selected from H, F, or C1-C3 alkoxy; More preferably, R2 is selected from H, F or methoxy.
[0008] In an optional embodiment, the compound has a structure shown in Formula II, Formula III or Formula IV:
[0009]
[0010]
[0011] Wherein, in Formula II, Formula III or Formula IV, R2 is as defined above;
[0012] In formula II, R3 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 Preferably, R3 is selected from H, halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; More preferably, R3 is selected from H, F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl.
[0013] In an optional embodiment, the compound comprises at least one of A1-A11:
[0014]
[0015] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the compound is 0.01%-2.5%, preferably 0.5%-1.5%.
[0016] In an optional embodiment, the electrolyte further includes a first additive, and the first additive includes an ethylene carbonate additive; optionally, the first additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, 1,2-difluoroethylene carbonate, and diethylene carbonate;
[0017] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.01%-3%, preferably 0.1%-2.0%.
[0018] In an optional embodiment, the electrolyte further includes a second additive, and the second additive includes a sulfate additive and / or a sulfonate additive; preferably, the second additive is selected from one or more of the following compounds:
[0019]
[0020]
[0021] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the second additive is 0.01%-5.0%, preferably 0.1%-4.0%.
[0022] In an optional embodiment, the electrolyte further comprises a lithium salt additive; preferably, the lithium salt additive comprises one or more of lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate;
[0023] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.01%-2%, preferably 0.1%-1.0%.
[0024] In a second aspect, the present application provides a secondary battery comprising a positive electrode active material, a negative electrode active material and the electrolyte described in the first aspect of the present application.
[0025] In an optional embodiment, the positive electrode active material includes lithium nickel cobalt manganese oxide and / or a lithium nickel cobalt manganese oxide derivative;
[0026] In an optional embodiment, the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials, and lithium-containing metal composite oxide materials.
[0027] The technical solution of this application has the following advantages:
[0028] The present application provides an electrolyte, which includes a solvent, an electrolyte salt and a compound having a structure shown in Formula I. By using a spirodienonesulfonyloxazole compound shown in Formula I, the lone electron pair on the N atom in the heterocyclic structure of the compound, when added to the electrolyte, will exhibit strong Lewis alkalinity, which can effectively inhibit the damage of HF in the electrolyte to the electrode interface, and at the same time form a stable solid interface film containing Li2SO3 inorganic components on the positive electrode surface, effectively inhibit the decomposition of the electrolyte, stabilize the transition metal on the surface of the positive electrode active material, reduce the oxidizability of the high-valent transition metal, and can also significantly improve the antioxidant property of the electrolyte, reduce the high-temperature gas production of the battery, thereby significantly improving the high-temperature storage performance, cycle performance and thermal shock performance of the battery.
[0029] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0030] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.
[0031] In the description of the present application, it should be noted that the orientation or positional relationship indicated by the terms "inside", "outside", etc. is based on the orientation or positional relationship shown, and is only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation of the present application. In addition, the terms "first", "second", and "third" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance.
[0032] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0033] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.
[0034] The present application provides an electrolyte and a secondary battery, wherein the electrolyte comprises a solvent, an electrolyte salt and a compound having a structure shown in Formula I. By adopting a spirodienonesulfonyloxazole compound shown in Formula I, the lone electron pair on the N atom in the heterocyclic structure of the compound, when added to the electrolyte, will exhibit a strong Lewis alkalinity, and can effectively inhibit the damage of HF in the electrolyte to the electrode interface, and at the same time form a stable solid interface film containing LiSO3 inorganic components on the positive electrode surface, effectively inhibiting the decomposition of the electrolyte, stabilizing the transition metal on the surface of the positive electrode active material, reducing the oxidizability of the high-valent transition metal, and can also significantly improve the oxidation resistance of the electrolyte, reduce the high-temperature gas production of the battery, thereby significantly improving the high-temperature storage performance, cycle performance and thermal shock performance of the battery.
[0035] Specifically, in a first aspect, the present application provides an electrolyte solution comprising a solvent, an electrolyte salt and a compound having a structure shown in Formula I:
[0036]
[0037] In Formula I, R1 is selected from unsubstituted or substituted C5 to C 15 aryl or unsubstituted or substituted C3~C 15 The heteroaryl group is selected from O, S, N or P; "substituted" means that the hydrogen atoms on the group are selected from halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy, C1-C 10 substituted by one or more of the haloalkyl of 1-C3; preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl, unsubstituted or substituted thienyl or unsubstituted or substituted furanyl, "substituted" means that the hydrogen atoms on the group are substituted by one or more selected from halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; more preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl or unsubstituted or substituted thienyl, "substituted" means that the hydrogen atoms on the group are substituted by F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl;
[0038] R2 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 Preferably, R2 is selected from H, F or C1-C3 alkoxy; More preferably, R2 is selected from H, F or methoxy.
[0039] The spirodienone sulfonyl oxazole compound shown in formula I has a lone electron pair on the N atom in the heterocyclic structure of the compound. When added to the electrolyte, it will show strong Lewis alkalinity, which can effectively inhibit the damage of HF in the electrolyte to the electrode interface. At the same time, the compound can form a stable solid interface film containing inorganic components such as Li2SO3, Li3N and Li2CO3 on the positive electrode surface through the sulfonyl group containing sulfur-oxygen double bonds and the spirodienone group, effectively inhibiting the decomposition of the electrolyte, stabilizing the transition metal on the surface of the positive electrode active material, reducing the oxidizability of the high-valent transition metal, and significantly improving the antioxidant property of the electrolyte, reducing the high-temperature gas production of the battery, thereby significantly improving the high-temperature storage performance, cycle performance and thermal shock performance of the battery. R1 is selected from unsubstituted or substituted C5~C 15 aryl or unsubstituted or substituted C3~C 15 The role of heteroaryl groups is that these aromatic or heteroaryl groups form copolymers through ring-opening polymerization after being oxidized, which can enhance the interface stability and improve the high-temperature storage performance. Compared with aromatic groups, heteroaryl groups are better.
[0040] In an optional embodiment, the compound has a structure shown in Formula II, Formula III or Formula IV:
[0041]
[0042]
[0043] Wherein, in Formula II, Formula III or Formula IV, R2 is as defined above;
[0044] In formula II, R3 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 Preferably, R3 is selected from H, halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; More preferably, R3 is selected from H, F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl.
[0045] For example, the compound comprises at least one of A1-A11:
[0046]
[0047] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the compound is 0.01%-2.5%. When the mass percentage of the compound of formula I is too high, the impedance of the electrolyte becomes large, causing lithium precipitation and resulting in a decrease in the low-temperature discharge performance of the battery. When the mass percentage of the compound of formula I is too low, the interface protection is insufficient, resulting in poor thermal shock performance, and also affects the cycle stability and low-temperature discharge performance. By controlling the mass percentage of the compound within the above range, the cycle stability can be improved while ensuring safety. For example, the mass percentage of the compound is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 2.5% or within the range composed of any two of the above values.
[0048] In an optional embodiment, the electrolyte further includes a first additive, and the first additive includes a vinyl carbonate additive; optionally, the first additive includes at least one of vinylene carbonate (VC), vinyl ethylene carbonate (VEC), fluoroethylene carbonate (FEC), trifluoromethylethylene carbonate (TFEC), 1,2-difluoroethylene carbonate (DFEC), and bis-ethylene carbonate (EC) (Chinese full name: [4,4'-bis-1,3-dioxane]-2,2'-dione, CAS number: 36205-45-5). Through the use of these first additives, LiF and / or lithium carbonate can be formed, the stability of the SEI film can be improved, and the high-temperature thermal stability of the battery can be improved. When used in combination with a compound having a structure shown in Formula I, the lithium conductivity of the SEI film is improved, and the thermal stability is improved, so that the high-temperature cycle performance, high-temperature storage performance, and low-temperature discharge performance are more significantly improved.
[0049] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the first additive is 0.01%-3%. When the mass percentage of the first additive is too high, the impedance of the electrolyte becomes larger, causing lithium precipitation, resulting in a decrease in the low-temperature discharge performance of the battery and a shortened high-temperature cycle life. When the mass percentage of the first additive is too low, the interface protection is insufficient, which will also affect the cycle stability. By controlling the mass percentage of the first additive within the above range, the cycle stability can be improved while ensuring safety. For example, the mass percentage of the first additive is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3% or within the range composed of any two of the above values.
[0050] In an optional embodiment, the electrolyte further includes a second additive, and the second additive includes a sulfate additive and / or a sulfonate additive. On the one hand, the second additive sulfate or sulfonate additive itself has a strong antioxidant ability, is not easily oxidized on the surface of the positive electrode material, and the sulfur-oxygen double bond can be reduced on the surface of the negative electrode to form a protective film, which effectively prevents the generation of electrolyte decomposition products and reduces the side reactions inside the battery, thereby further enhancing the protection of active materials and improving the high-temperature storage performance and cycle performance of the battery. On the other hand, when sulfate additives and / or sulfonate additives are used in combination with spirodienonesulfonyloxazole compounds, the content of Li2SO4 and Li2SO3 inorganic components of the SEI film can be increased, further improving the high and low temperature discharge performance. For example, the second additive is selected from one or more of the following compounds:
[0051]
[0052]
[0053] In an optional embodiment, the mass percentage of the second additive is 0.01%-5% based on the total mass of the electrolyte. When the mass percentage of the second additive is too high, the impedance of the electrolyte becomes larger, and lithium precipitation is induced, which will lead to a decrease in the low-temperature discharge performance of the battery, a shortened cycle life, and may cause safety problems. When the mass percentage of the second additive is too low, the interface protection is insufficient, which will also affect the cycle stability. By controlling the mass percentage of the second additive within the above range, the cycle stability can be improved while ensuring safety. For example, the mass percentage of the second additive is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2%, 3%, 5% or in the range composed of any two of the above values.
[0054] In an optional embodiment, the electrolyte further includes a lithium salt additive, and the lithium salt additive includes one or more of lithium difluorophosphate (LiPO2F2), lithium difluorooxalate borate (LiODFB), lithium difluorophosphate, lithium tetrafluoroborate, and lithium tetrafluorophosphate. When the lithium salt additive is further added to the electrolyte, the lithium salt additive comprising lithium difluorophosphate, lithium difluorophosphate borate (LiODFB), lithium difluorophosphate, lithium tetrafluoroborate, and lithium tetrafluorophosphate can inhibit the oxidative decomposition of the electrolyte and the interface film impedance is small, thereby maintaining the high temperature cycle performance at a high level. On the basis of improving the low temperature discharge performance of the battery. Therefore, when the lithium salt additive is used in combination with the compound having the structure shown in Formula I, the first additive, and the second additive, the high temperature and low temperature discharge performance of the battery can be taken into account at the same time.
[0055] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.01%-2%. When the mass percentage of the lithium salt additive is too high, the impedance of the electrolyte becomes larger, causing lithium precipitation and resulting in a decrease in the low-temperature discharge performance of the battery. When the mass percentage of the lithium salt additive is too low, the interface protection is insufficient, which will also affect the cycle stability. By controlling the mass percentage of the lithium salt additive within the above range, the cycle stability can be improved while ensuring safety. For example, the mass percentage of the lithium salt additive is 0.01%, 0.05%, 0.1%, 0.5%, 1%, 2% or within the range composed of any two of the above values.
[0056] In an optional embodiment, the solvent comprises a cyclic carbonate and a chain carbonate; preferably, the cyclic carbonate comprises one or more of ethylene carbonate, propylene carbonate, and fluoroethylene carbonate; preferably, the chain carbonate comprises one or more of ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, propyl propionate, ethyl propionate, ethyl acetate, and methyl acetate.
[0057] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the solvent is 70%-90%.
[0058] In an optional embodiment, the electrolyte salt comprises a lithium salt; preferably, the lithium salt includes one or more of lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium tetrafluoroborate (LiBF4), and lithium bis(oxalatoborate) (LiBOB).
[0059] In an optional embodiment, based on the total mass of the electrolyte, the mass percentage of the lithium salt is 8%-20%.
[0060] In an optional embodiment, the present invention also provides a method for preparing the above-mentioned electrolyte, the method comprising the following steps:
[0061] An organic solvent, an electrolyte salt and a compound having a structure shown in Formula I are mixed to obtain the electrolyte.
[0062] In an optional embodiment, the present invention also provides another method for preparing the above-mentioned electrolyte, the method comprising the following steps:
[0063] The electrolyte solution is obtained by mixing an organic solvent, an electrolyte salt and a compound having a structure shown in Formula I with one or more of a first additive, a second additive and a lithium salt additive.
[0064] In a second aspect, the present application provides a secondary battery comprising a positive electrode active material, a negative electrode active material and the electrolyte described in the first aspect of the present application.
[0065] In an optional embodiment, the positive electrode active material includes lithium nickel cobalt manganese oxide and / or a lithium nickel cobalt manganese oxide derivative. The lithium nickel cobalt manganese oxide has the following chemical formula: Li(Ni x Co y Mn z )O2, wherein x+y+z=1, 0.8≤x<1, 0<y<0.2, 0<z<0.2, for example, the molecular formula of lithium nickel cobalt manganese oxide is LiNi 0.8 Co 0.1 Mn 0.1 O2 or LiNi 0.88 Co 0.1 Mn 0.02 O2. The lithium nickel cobalt manganese oxide derivative refers to lithium nickel cobalt manganese oxide coated or doped with other metal elements, wherein the other metal elements include at least one of Zr, Ti, Sr, W, Mg, Sn, Y, Al, Ta, Si, La, V, Ca, Gd, Ce, Ba, Nb, Er, Nd, Mo, and Cr. For example, the lithium nickel cobalt manganese oxide derivative can be Li 1.0 Ni 0.8982 Co 0.0589 Mn 0.0409 Zr 0.00 2O2.
[0066] In an optional embodiment, the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microbeads, silicon-based negative electrode materials, and lithium-containing metal composite oxide materials.
[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0068] Preparation Example 1
[0069] The preparation method of compound A1 is as follows:
[0070]
[0071] (1) Benzoic acid (5 mmol), p-methoxybenzenesulfonamide (5 mmol), 4-dimethylaminopyridine (DMAP, 7.5 mmol) and dichloromethane (DCM, 50 mL) were added to a round-bottom flask. EDC (1-ethyl-(3-dimethylaminopropyl)carbodiimide, 6 mmol) was dissolved in 60 mL DCM solvent under nitrogen atmosphere, added dropwise to the above solution, and stirred at room temperature for 16 h. The reaction was then quenched with 2 mol / L hydrochloric acid solution and extracted with DCM. The combined organic extracts were washed with brine, dried over Na2SO4, and concentrated in vacuo to obtain a crude residue. The crude residue was further purified by recrystallization from DCM / petroleum ether (PE) (volume ratio 10:1) to obtain the substrate.
[0072]
[0073] (2) Electrolysis was performed using an electrochemical continuous flow cell with a constant current of 130 mA. The cell was equipped with a graphite anode and a nickel cathode, each with a surface area of 10 cm 2 , the distance between electrodes is 250μm. The substrate (the substrate prepared in step (1) with a concentration of 0.04mol / L methanol solution) is injected into the electrochemical continuous flow cell using a syringe pump with a flow rate of 0.5mL / min. At the beginning, the system is stable for 2 minutes. After reaching a stable state, the outlet solution is collected for 20 minutes (10mL). The formation of bubbles in the tube can be observed during the reaction. HCl solution (concentration of 2mol / L, 2mL) is added to the reaction mixture and kept stirring for 0.5 hours. The reaction mixture is then concentrated in vacuo, and the crude residue is separated by rapid column chromatography on silica gel (the volume ratio of ethyl acetate to cyclohexane is 10:1) to obtain compound A1.
[0074] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A1 are as follows:
[0075] IR(pure substance,cm -1 ):3062(w),1673(m),1640(s),1571(s),1452(m),1322(s),1295(s),1170(s),1109(m),1091(m),961(s),868(m),692(s),591(w),474(s);
[0076] 1 H NMR (400 MHz, deuterated chloroform) δ 8.12 (d, J = 7.3 Hz, 2H), 7.75 (t, J = 7.5 Hz, 1H), 7.57 (t, J = 7.9 Hz, 2H), 6.83 (d, J = 10.2 Hz, 2H), 6.58 (d, J = 10.2 Hz, 2H);
[0077] 13 C NMR (101 MHz, deuterated chloroform) δ 182.9, 166.4, 136.8, 136.1, 133.5, 130.4, 129.4, 124.1, 85.5;
[0078] HRMS(ESI)C 13 H 10 NO4S + [M + H + ]Theoretical value: 276.0325; measured value: 276.0326.
[0079] Preparation Example 2
[0080] The method is basically the same as Preparation Example 1, except that p-toluic acid is used instead of benzoic acid to prepare Compound A2.
[0081] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A2 are as follows:
[0082] IR(neat,cm -1 ):3065(w),1673(s),1599(s),1507(w),1347(m),1293(s),1166(s),1095(s),960(m),863(m),729(m),617(w),592(w),531(w),465(w);
[0083] 1 H NMR (400 MHz, deuterated chloroform) δ 8.01 (d, J = 8.4 Hz, 2H), 7.36 (d, J = 8.4 Hz, 2H), 6.83 (d, J = 10.2 Hz, 2H), 6.59 (d, J = 10.3 Hz, 2H), 2.48 (s, 3H);
[0084] 13 C NMR (101 MHz, deuterated chloroform) δ 183.0, 166.5, 147.8, 137.0, 133.4, 130.5, 130.2, 121.2, 85.4, 22.2;
[0085] HRMS(ESI)C 14 H 12 NO4S + [M + H + ]Theoretical value: 290.0482; measured value: 290.0476.
[0086] Preparation Example 3
[0087] The method is basically the same as Preparation Example 1, except that o-fluorobenzoic acid is used instead of benzoic acid to prepare Compound A5.
[0088] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A5 are as follows:
[0089] IR(neat,cm -1 ):3065(w),1674(m),1601(s),1561(m),1401(m),1350(m),1295(m),1168(s),1093(s),1091(m),961(m),861(m),731(m),612(m),531(w);
[0090] 1 H NMR (400 MHz, deuterated chloroform) δ 8.07 (d, J = 8.2 Hz, 1H), 7.79-7.69 (m, 1H), 7.39-7.24 (m, 2H), 6.84 (d, J = 10.2 Hz, 2H), 6.61 (d, J = 10.2 Hz, 2H);
[0091] 13 C NMR (101 MHz, deuterated chloroform) δ 182.8, 164.1 (d, J = 5.0 Hz), 162.7 (d, J = 266.9 Hz), 138.0 (d, J = 9.5 Hz), 136.6, 133.7, 132.5, 125.1 (d, J = 4.0 Hz), 117.9 (d, J = 21.3 Hz), 112.8 (d, J = 8.4 Hz), 84.7;
[0092] HRMS(ESI)C 13 H8FNNaO4S + [M + Na + ]Theoretical value: 316.0050; measured value: 316.0046.
[0093] Preparation Example 4
[0094] The method is basically the same as Preparation Example 1, except that 4-trifluoromethylbenzoic acid is used instead of benzoic acid to prepare Compound A8.
[0095] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A8 are as follows:
[0096] 1 H NMR (400 MHz, deuterated chloroform) δ 8.26 (d, J = 8.4 Hz, 2H), 7.84 (d, J = 8.5 Hz, 2H), 6.83 (d, J = 10.3 Hz, 2H), 6.63 (d, J = 10.2 Hz, 2H);
[0097] 13 C NMR (126 MHz, deuterated chloroform) δ 182.7, 165.1, 137.2 (q, J = 33.2 Hz), 136.2, 133.8, 130.8, 127.5, 126.5 (q, J = 3.6 Hz), 123.2 (q, J = 273.4 Hz), 85.9;
[0098] HRMS(ESI)C 14 H9F3NO4S + [M + H + ]Theoretical value: 344.0199; measured value: 344.0198.
[0099] Preparation Example 5
[0100] The process is basically the same as Preparation Example 1, except that 2-thiophenecarboxylic acid is used instead of benzoic acid to prepare Compound A9.
[0101] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A9 are as follows:
[0102] IR(neat,cm -1 ):3100(w),1672(s),1589(s),1412(m),1345(s),1277(m),1166(s),1075(s),957(m),855(m),733(m),611(m),592(w),520(m),474(m);
[0103] 1 H NMR (500 MHz, deuterated chloroform) δ 8.05 (dd, J = 3.9, 1.4 Hz, 1H), 7.91 (dd, J = 5.0, 1.3 Hz, 1H), 7.29-7.27 (m, 1H), 6.84 (d, J = 10.2 Hz, 2H), 6.60 (d, J = 10.2 Hz, 2H);
[0104] 13 C NMR (126 MHz, deuterated chloroform) δ 182.9, 161.9, 137.8, 137.1, 136.8, 133.6, 129.4, 126.3, 85.5.
[0105] HRMS(ESI)C 11 H8NO4S2 + [M + H + ]Theoretical value: 281.9889; measured value: 281.9881.
[0106] Preparation Example 6
[0107] The process is basically the same as Preparation Example 1, except that 3-fluoro-4-methoxybenzenesulfonamide is used instead of p-methoxybenzenesulfonamide to prepare Compound A10.
[0108] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A10 are as follows:
[0109] IR(neat,cm -1 ):3062(w),1673(m),1604(s),1571(s),1452(m),1322(s),1295(s),1170(s),1109(m),1091(m),961(s),868(m),692(s),591(w),474(s);
[0110] 1 H NMR (400 MHz, deuterated chloroform) δ 8.13 (d, J = 7.4 Hz, 2H), 7.77 (t, J = 7.5 Hz, 1H), 7.58 (t, J = 7.9 Hz, 2H), 6.88 (dd, J = 10.2, 3.0 Hz, 1H), 6.61 (dd, J = 10.2, 6.4 Hz, 1H), 6.44 (dd, J = 9.8, 3.0 Hz, 1H);
[0111] 13 C NMR (101 MHz, deuterated chloroform) δ 176.0 (d, J = 22.7 Hz), 166.19, 155.6 (d, J = 278.4 Hz), 137.9 (d, J = 2.2 Hz), 136.3, 132.3 (d, J = 3.3 Hz), 130.5, 129.5, 123.9, 114.5 (d, J = 19.8 Hz), 87.2 (d, J = 10.3 Hz);
[0112] HRMS(ESI)C 13 H9NO4S + [M + H + ]Theoretical value: 294.0231; measured value: 294.0235.
[0113] Preparation Example 7
[0114] The process is basically the same as Preparation Example 1, except that 3,4-dimethoxybenzene-1-sulfonamide is used instead of p-methoxybenzenesulfonamide to prepare Compound A11.
[0115] The infrared, nuclear magnetic resonance and mass spectrometry data of compound A11 are as follows:
[0116] IR(neat,cm -1 ):3069(w),1683(m),1608(s),1570(m),1452(m),1322(m),1288(m),1168(s),1025(m),949(m),852(m),697(s),639(m),569(m),480(w);
[0117] 1 H NMR (400 MHz, deuterated chloroform) δ 8.13 (d, J = 7.2 Hz, 2H), 7.79-7.70 (m, 1H), 7.57 (t, J = 7.9 Hz, 2H), 6.86 (dd, J = 10.2, 3.0 Hz, 1H), 6.57 (d, J = 10.0 Hz, 1H), 5.69 (d, J = 3.0 Hz, 1H), 3.81 (s, 3H);
[0118] 13 C NMR (101 MHz, deuterated chloroform) δ 178.4, 166.6, 154.1, 137.6, 136.0, 132.6, 130.4, 129.4, 124.5, 103.8, 88.3, 56.1.
[0119] HRMS(ESI)C 14 H 12 NO4S + [M + H + ]Theoretical value: 306.0431; measured value: 306.0421.
[0120] Compounds B1 and B18 are both commercially available products.
[0121] Example 1
[0122] The present embodiment provides an electrolyte, and the preparation method thereof is as follows: in a glove box filled with argon gas (water content <10ppm, oxygen content <1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed evenly, and fully dried lithium hexafluorophosphate with a total mass percentage of 14.5wt% based on the total mass percentage of the electrolyte and a compound with a structure shown in formula I (referred to as "compound of formula I", compound A1 in this embodiment) with a total mass percentage of 1wt% based on the total mass percentage of the electrolyte are quickly added to the mixed solution, wherein the mass ratio of EC, EMC and DEC is 30:50:20. The mixed solution is stirred evenly to obtain an electrolyte.
[0123] This embodiment also provides a lithium-ion battery, including the above electrolyte, and also including a positive electrode sheet and a negative electrode sheet, wherein the positive electrode sheet is prepared by the following method: lithium nickel cobalt manganese oxide (LiNi0.8 Co 0.1 Mn 0.1 O2), conductive carbon (Super-P) and polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone in a mass ratio of 96.5:2:1.5, stirred evenly, and a positive electrode slurry is obtained. The slurry is coated on a carbon-coated aluminum foil with a thickness of about 12 μm, dried, cold pressed, and then cut into pieces and welded to the pole ears to obtain a positive electrode sheet. The preparation method of the negative electrode sheet is as follows: Graphite, conductive carbon (Super-P), styrene-butadiene rubber and sodium carboxymethyl cellulose (CMC) are mixed in a solvent deionized water in a mass ratio of about 96.8:1.5:1:0.7, stirred evenly, and a negative electrode slurry is obtained. The slurry is coated on a carbon-coated copper foil with a thickness of about 8 μm, dried, cold pressed, and then cut into pieces and welded to the pole ears to obtain a negative electrode sheet.
[0124] The preparation method of lithium-ion battery is as follows: the prepared positive electrode plate, separator (formed by base film), and negative electrode plate are stacked by Z-type stacking machine to obtain bare battery cells without liquid injection; the bare battery cells are placed in outer packaging foil, and the prepared electrolyte is injected into the dried bare battery cells. After vacuum packaging, standing, formation, secondary sealing, sorting and other conventional processes, the required lithium-ion battery is obtained.
[0125] The preparation methods of the electrolytes in Examples 2-5 are substantially the same as those in Example 1. Based on the total mass of the electrolytes, the mass percentages of the compounds of Formula I are different, as shown in Table 1.
[0126] The preparation methods of the electrolytes in Examples 6-11 are substantially the same as those in Example 1, except that the types of the compounds of Formula I are different, as shown in Table 1.
[0127] The preparation method of the electrolyte in Examples 12-30 is basically the same as that in Example 1, except that it also includes one or more of the first additive, the second additive, and the lithium salt additive. The specific type of each additive and the mass percentage based on the total mass of the electrolyte are detailed in Table 1.
[0128] The preparation method of the electrolyte in Example 31 is basically the same as that in Example 1, except that the type and mass ratio of the solvent are different, see Table 1 for details.
[0129] The preparation method of the electrolyte in Examples 32-33 is basically the same as that in Example 1, except that the mass percentage of the lithium salt based on the total mass of the electrolyte is different, see Table 1 for details.
[0130] The preparation method of the electrode solution and the secondary battery in Comparative Example 1 is substantially the same as that in Example 1, except that Compound A1 is omitted from the electrolyte.
[0131] Table 1 Mass type and mass percentage of each substance in the electrolyte
[0132]
[0133]
[0134]
[0135] “ / ” means it does not exist.
[0136] Test Case
[0137] (1) High temperature cycle performance test
[0138] At 45°C, the lithium-ion battery is charged at a constant current of 1C (nominal capacity) to a voltage of 4.2V, then charged at a constant voltage of 4.2V to a current of 0.05C, left for 10 minutes, and then discharged at a constant current of 1C to a cut-off voltage of 2.8V. The above is one charge and discharge cycle. The lithium-ion battery is subjected to 500 charge and discharge cycles at 25°C and 500 charge and discharge cycles at 45°C under the above conditions.
[0139] The capacity retention rate (%) of a lithium-ion battery after N cycles = (discharge capacity at the Nth cycle / initial discharge capacity) × 100%, where N is the number of cycles of the lithium-ion battery.
[0140] (2) 60℃ 14d high temperature storage test
[0141] The battery was placed at room temperature and charged and discharged once at 1C (4.20V~2.8V), and the discharge capacity C0 of the battery before storage was recorded. Then the battery was charged to a full charge state of 4.20V with constant current and constant voltage. The thickness d1 of the battery before high-temperature storage was tested with a vernier caliper (the two diagonals of the above battery were connected by a straight line, and the intersection of the two diagonals was the battery thickness test point). The battery was placed in a 60℃ constant temperature box and stored for 14 days. After the storage was completed, the battery was taken out and the thermal thickness d2 of the battery after storage was tested. The battery thickness expansion rate after storage at 60℃ for 14 days was calculated. After the battery was cooled at room temperature for 24h, the battery was discharged to 2.8V at 1C again, and then charged to 4.20V at 1C constant current. The discharge capacity C1 and charge capacity C2 of the battery after storage were recorded, and the capacity remaining rate and recovery rate of the battery after storage at 60℃ for 14 days were calculated as follows:
[0142] Thickness expansion ratio after storage at 60°C for 14 days = (d2-d1) / d1*100%;
[0143] Residual capacity retention after storage at 60°C for 14 days = C1 / C0*100%;
[0144] After storage at 60°C for 14 days, the recovery capacity retention rate = C2 / C0*100%.
[0145] (3) Lithium-ion battery low temperature (-10°C) rate discharge performance test
[0146] At 25°C, the lithium-ion battery was discharged at a constant current of 0.5C to a cut-off voltage of 2.8V. After standing for 10 minutes, it was charged at a constant current and constant voltage of 1C to 4.2V with a cut-off current of 0.05C. The battery cell was moved to a -10°C high and low temperature box. After standing for 120 minutes, it was discharged at a constant current of 4C / 7C to a cut-off voltage of 2.8V, and the inflection point voltage was recorded.
[0147] (4) Thermal shock performance
[0148] Under 25℃ environmental conditions, discharge to 2.8V with a given current of 0.2C; leave for 5min; charge to 4.20V with a charging current of 0.2C. When the cell voltage reaches 4.20V, change to 4.20V constant voltage charging until the charging current is less than or equal to the given cut-off current of 0.05C; after leaving for 1h, put the cell into the oven, and the oven temperature rises to 135±2℃ at a rate of 5±2℃ / min, and stops after keeping for 30min. The judgment standard is that the cell does not catch fire or explode. Test 5 batteries in each group, and record the number of batteries that pass the test / total number of tests. Please see Table 2 for the results of the above tests.
[0149] Table 2 Electrical properties of lithium-ion secondary batteries
[0150]
[0151]
[0152] As shown in Table 2, the above examples and comparative examples show that the examples containing the compound of formula I significantly improve thermal shock performance, high temperature cycle and storage performance. Comparison of the examples shows that with the addition of one or more of the first additive, the second additive and the lithium salt additive, the thermal stability of the positive and negative electrode interfaces is further optimized or the impedance performance is reduced, so that the battery has better high temperature cycle, storage, low temperature discharge and thermal shock performance.
[0153] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.
Claims
1. An electrolyte, characterized in that: The electrolyte comprises a solvent, an electrolyte salt and a compound having a structure shown in Formula I: In Formula I, R1 is selected from unsubstituted or substituted C5 to C 15 aryl or unsubstituted or substituted C3~C 15 The heteroaryl group is selected from O, S, N or P; "substituted" means that the hydrogen atoms on the group are selected from halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy, C1-C 10 Preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl, unsubstituted or substituted thienyl or unsubstituted or substituted furanyl, "substituted" means that the hydrogen atoms on the group are substituted by one or more selected from halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; More preferably, R1 is selected from unsubstituted or substituted phenyl, unsubstituted or substituted naphthyl or unsubstituted or substituted thienyl, "substituted" means that the hydrogen atoms on the group are substituted by F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl; R2 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 Preferably, R2 is selected from H, F or C1-C3 alkoxy; More preferably, R2 is selected from H, F or methoxy.
2. The electrolyte according to claim 1, characterized in that The compound has a structure shown in Formula II, Formula III or Formula IV: Wherein, in Formula II, Formula III or Formula IV, R2 is as defined in claim 1; In formula II, R3 is selected from H, halogen, C1-C 10 Alkyl, C1-C 10 Alkoxy or C1-C 10 preferably, R3 is selected from H, halogen, C1-C3 alkyl, C1-C3 alkoxy, C1-C3 haloalkyl; more preferably, R3 is selected from H, F, methyl, ethyl, methoxy, tert-butyl or trifluoromethyl.
3. The electrolyte according to claim 1 or 2, characterized in that The compound comprises at least one of A1-A11:
4. The electrolyte according to any one of claims 1 to 3, characterized in that: Based on the total mass of the electrolyte, the mass percentage of the compound is 0.01%-2.5%, preferably 0.5%-1.5%.
5. The electrolyte according to any one of claims 1 to 4, characterized in that: The electrolyte also includes a first additive, which includes an ethylene carbonate additive; optionally, the first additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, 1,2-difluoroethylene carbonate, and diethylene carbonate.
6. The electrolyte according to claim 5, characterized in that Based on the total mass of the electrolyte, the mass percentage of the first additive is 0.01%-3%, preferably 0.1%-2.0%.
7. The electrolyte according to any one of claims 1 to 6, characterized in that: The electrolyte further includes a second additive, which includes a sulfate additive and / or a sulfonate additive; preferably, the second additive is selected from one or more of the following compounds:
8. The electrolyte according to claim 7, characterized in that Based on the total mass of the electrolyte, the mass percentage of the second additive is 0.01%-5.0%, preferably 0.1%-4.0%.
9. The electrolyte according to any one of claims 1 to 8, characterized in that: The electrolyte further includes a lithium salt additive, wherein the lithium salt additive includes one or more of lithium difluorophosphate, lithium difluorooxalatoborate (LiODFB), lithium difluorooxalatophosphate, lithium tetrafluoroborate, and lithium tetrafluorooxalatophosphate; Preferably, based on the total mass of the electrolyte, the mass percentage of the lithium salt additive is 0.01%-2%, more preferably 0.1%-1.0%.
10. A secondary battery, characterized in that: Comprising a positive electrode active material, a negative electrode active material and an electrolyte as claimed in any one of claims 1 to 9; Preferably, the positive electrode active material comprises lithium nickel cobalt manganese oxide and / or a lithium nickel cobalt manganese oxide derivative; Preferably, the negative electrode active material includes one or more of artificial graphite, natural graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials, and lithium-containing metal composite oxide materials.